Comparing Japan's and the Republic of Korea's missile defense strategies using neoclassical realism - Seah, Charlotte Ning (Nanyang Technological University, 2023)
Japan and the Republic of Korea (ROK) are currently facing a progressively tense international security environment, especially from its neighbors, China and the Democratic People’s Republic of Korea. In response, Japan and ROK have implemented respective missile defense (MD) strategies to ensure that they are well prepared to counter any missile strikes from their adversaries. Yet, despite both being the United States’ (US’) allies and sharing similar cultures and external threats, the two countries differ in their MD strategies. On the one hand, Japan established a joint development of MD strategies with the US. On the other hand, ROK has largely refused US cooperation and instead developed an independent MD policy. This divergence motivates the question: why do Japan and ROK employ such different MD strategies? More specifically, why did they pursue different levels of cooperation with the US in their respective MD systems? This paper utilizes Neoclassical Realism and postulates that the difference in the countries’ domestic factors, framed by their systemic stimuli, has contributed to this divergence in MD strategies.